Analisis Profit Margin, Price Earning ratio dan Earning Per Price Terhadap Return On Investment Pada Perusahaan SubSektor Rokok tahun 2019-2023 - Salsabila, Shofia; Edy Sujana; Wiguna, I Gd Nandra Hary (Vokasi : Jurnal Riset Akuntansi, 2025)
This study aims to analyze the influence of Profit Margin, Price Earning Ratio (PER), and Earning Per Share (EPS) on Return on Investment (ROI) in cigarette sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. The cigarette sub-sector was selected due to its significant economic contribution, despite facing challenges such as strict regulations and social pressure, making financial ratio analysis essential in evaluating investment performance. This research adopts a quantitative approach using multiple linear regression. Data were obtained from company financial statements selected through purposive sampling. The results show that individually, Profit Margin, PER, and EPS have a positive and significant effect on ROI. Profit Margin reflects operational efficiency, PER indicates market perception of company valuation, and EPS demonstrates the company’s ability to generate profit per share. Simultaneously, these three variables also have a significant effect on ROI. These findings suggest that the combination of these financial ratios serves as a critical indicator for assessing and improving investment returns. This study is expected to serve as a reference for investors and company management in making more accurate and measurable financial decisions..